2007
DOI: 10.1002/jcp.21136
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Fas‐mediated apoptosis in Type II cells by high doses of hepatocyte growth factor bypasses the mitochondrial requirement

Abstract: The death receptor pathway is coupled to the mitochondria apoptosis pathway. However, mitochondrial participation, which is stimulated by Bid but suppressed by Bcl-2/Bcl-x L , is required in certain cells (Type II), but not in others (Type I). While these differences were originally characterized in the lymphoid cell lines, the typical Type II cells are represented by hepatocytes in vivo. The molecular mechanisms that distinguish Type II from Type I cells and the regulation are not fully understood. Fas can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In response to high levels of HGF or FasL, c‐Met is released from Fas, allowing FADD and caspase‐8 recruitment and apoptosis induction 35, 36. Interestingly, a recent report showed that high doses of HGF could bypass the mitochondrial requirement for Fas‐induced apoptosis in Jurkat cells and hepatocytes, leading to a type I signaling phenotype 37. Similarly, integrins could modulate the Fas, but not the TNF‐R1 DISC to engage type I instead of type II signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In response to high levels of HGF or FasL, c‐Met is released from Fas, allowing FADD and caspase‐8 recruitment and apoptosis induction 35, 36. Interestingly, a recent report showed that high doses of HGF could bypass the mitochondrial requirement for Fas‐induced apoptosis in Jurkat cells and hepatocytes, leading to a type I signaling phenotype 37. Similarly, integrins could modulate the Fas, but not the TNF‐R1 DISC to engage type I instead of type II signaling.…”
Section: Discussionmentioning
confidence: 99%
“…c-MET with FAS complex was also found in hepatoblastoma cells and breast neoplastic cells (Wang et al 2002), in normal B lymphocytes and in pediatric B acute lymphoblastic leukemia cells (REH) (Accordi et al 2007) as well as in some types of lymphoid cells (Zhao et al 2007).…”
Section: Interaction Of C-met With Death Receptors During Hgfinduced mentioning
confidence: 99%
“…103 Many papers have reported that c-Met and HGF are expressed together. [115][116][117][118] It was completely understood in two hepatocyte carcinoma cells lines, hepa-1 wild-type (c1c7) and the subunit mutated (c4) lacking hypoxia inducible factor-1 (HIF-1) that they are very susceptible to apoptosis by HGF. [104][105][106][107] Tumour biology reveals that there are two most important signal transduction pathways for c-Met ⁄ HGF multifunctional effects, mitogen-activated protein kinase (MAPK), and phosphoinositide 3-kinase (PI3K).…”
Section: Hepatocyte Growth Factor (Hgf)mentioning
confidence: 99%
“…113,114 However, apoptotic effects of HGF ⁄ c-Met is not yet fully understood, but it has been observed in number of cell lines such as ovarian carcinoma cell, breast carcinoma cell, mouse sarcoma cell, and mouse hepatocarcinoma cell. [115][116][117][118] It was completely understood in two hepatocyte carcinoma cells lines, hepa-1 wild-type (c1c7) and the subunit mutated (c4) lacking hypoxia inducible factor-1 (HIF-1) that they are very susceptible to apoptosis by HGF. In this case, p53, c-Myc progressively decreased, whereas, JNK1, caspase8, cytochrome c, and caspase 3 levels, are increased.…”
Section: Hepatocyte Growth Factor (Hgf)mentioning
confidence: 99%